Extractive multi document summarization using harmony search algorithm - Zuhair Hussein Ali; Ahmed Kawther Hussein; Haithem Kareem Abass; Elham Fadel (Universitas Ahmad Dahlan, 2021)
The exponential growth of information on the internet makes it troublesome for users to get valuable information. Text summarization is the process to overcome such a problem. An adequate summary must have wide coverage, high diversity, and high readability. In this article, a new method for multi-document summarization has been supposed based on a harmony search algorithm that optimizes the coverage, diversity, and readability. Concerning the benchmark dataset Text Analysis Conference (TAC-2011), the ROUGE package used to measure the effectiveness of the proposed model. The calculated results support the effectiveness of the proposed approach.